Hepatic pulmonary fusion: A rare case - Kirtane Jyotsna; Mukunda R; Bendre Pradyna; Taide Devendra (Wolters Kluwer Medknow Publications, 2010)
This paper describes a rare case of a seven-month-old infant with right-sided congenital diaphragmatic hernia, who was found to have fusion of his herniated part of liver with lower lobe of right lung. The report describes clinical presentation and successful surgical management along with a review of the world literature.